Шаги в пустоте - Лавряшина Юлия Александровна (Тень логова, 2023)
Экземпляры: аб. ЦБ (20240520) / Инвентарный номер: 19227 / Цена: / Сис.шифр: 84(2Рос=411.2)6 / Авт.знак: Л 13 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=411.2)6-4